A level set model for simulating fatigue-driven delamination in composites. (November 2015) - Latifi, M.; van der Meer, F.P.; Sluys, L.J.
Highlights: A level set model for simulating fatigue-driven delamination is proposed. The model is developed based on the fracture mechanics theory. In contrast with cohesive methods Paris law implementation is straightforward. In contrast with VCCT the crack front location is mesh-independent. The model can predict delamination growth rate and its front shape in composites. Abstract: This paper proposes a level set model for simulating delamination propagation in composites under high-cycle fatigue loading. For quasi-static loading conditions, interface elements with a cohesive law are widely used for the simulation of delamination. However, basic concepts from fatigue analysis such as the notion that the crack growth rate is a function of energy release rate cannot be embedded in existing cohesive laws. Therefore, we propose a model in which the cohesive zone is eliminated from the computation while maintaining the flexibility that the crack shape is not bound to element edges. The model is able to predict the delamination growth rate and its front shape accurately. To demonstrate the validity of the model, several tests under different fracture modes are conducted and the results are compared with experimental data, analytical solutions and results from cohesive zone analysis.